Reassesment of the Fecundity of California Sheephead - Loke-Smith, Kerri A. (Mar Coast Fish, 2012)
Fecundity estimates used in a 2004 stock assessment to evaluate the overall health of the population of California sheephead Semicossyphus pulcher were based primarily on two studies. The first estimated the total fecundity of only nine individuals captured near Santa Catalina Island, California, and the second estimated batch fecundity of individuals taken from only one artificial reef. In order to develop a current and more comprehensive estimate of fecundity, we collected California sheephead from seven locations off southern California throughout the spawning season (July through September). To estimate both total fecundity and batch fecundity, we categorized and counted oocytes from ovarian subsamples of 28 and 24 (respectively) mature females (stage 3, spawning capable; determined by histological analysis). Total and batch fecundity increased with somatic mass, standard length, and ovary mass. We found total fecundity to increase with somatic mass to a power of 5.5, which is considerably greater than the value (2.95) reported previously. Our observations therefore highlight the importance of large females in the reproductive potential of the California sheephead stock. Regression analysis indicates that ovary mass is the most accurate biological indicator of fecundity for California sheephead and should be used for subsequent stock analyses.